ANALISIS VALUE FOR MONEY DALAM MEWUJUDKAN EFISIENSI, TRANSPARANSI, DAN AKUNTABILITAS FISKAL: (TRANSFORMASI DIGITAL ADMINISTRASI PBB-P2) - Elsa Farista; Eva Nur Atika Devi; Mahbubah Subairi; Mohamad Djasuli (Politeknik Negeri Ambon, 2025)
Introduction: The development of digital technology has brought significant transformation in tax administration, including Rural and Urban Land and Building Tax, but its implementation faces both challenges and opportunities. This study aims to analyze the challenges and opportunities of digitizing the administration of Rural and Urban Land and Building Tax to improve the efficiency and transparency of the tax system. Methods: The method used is a systematic literature study with content analysis of published sources between 2020 and 2024. Results: The novelty of this research lies in the holistic approach that combines technical and social aspects together, in contrast to previous studies that tend to discuss both aspects separately. The results reveal that the main challenges include limited internet infrastructure, low technological literacy, and unpreparedness of government officials, while the opportunities include improving administrative efficiency, transparency, and accountability through technological innovations such as the Local Tax Management Information System and the Indonesian Standard Quick Response Code. The research conclusion shows that the digitalization of Rural and Urban Land and Building Tax administration has the potential to improve the tax system if the challenges of infrastructure, literacy, and human resource capacity can be overcome. Recommendations for future research include empirical field studies, expanding data coverage, exploring the impact of digitization on specific groups, and integrating the latest technologies such as artificial intelligence and block chains in the tax system. Keywords: Digitalization; PBB-P2; Tax Administration; challenges; opportunities.